2017
DOI: 10.17222/mit.2015.319
|View full text |Cite
|
Sign up to set email alerts
|

Tensile behaviour and fractography analyses of LM6/ZrO2 composites

Abstract: Aluminium-based metal matrix (LM6) composite materials were prepared using various percentages of 0 %, 3 %, 6 %, 9 % and 12 % of zirconia by the weight fraction method and fabricated by the stir casting method. Five samples were prepared as per the ASTM B-557-M-94 standard, and then the prepared sample was subjected to an energy-dispersive spectrometry (EDS), hardness and tensile tests. The hardness and tensile test results revealed that the maximum hardness, maximum ultimate strength, yield strength was obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Among these methods Stir casting technique is used to produce the composites in economical way, high production rate at the very simple manner. It also increases the uniform distribution of particles and reduces the defects such as porosity, weak bonding between matrix and reinforcement [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these methods Stir casting technique is used to produce the composites in economical way, high production rate at the very simple manner. It also increases the uniform distribution of particles and reduces the defects such as porosity, weak bonding between matrix and reinforcement [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The reinforcement of ZrO 2 is very attractive as it exhibits a density of 8.18 gm/cm 3 , melting point 1860˚C, UTS-425 MPa, VHN-150, Young's modulus of 98 GPa. It was also found that ZrO 2 shows better strength, hardness and fracture toughness with slight reduction in ductility [18,[20][21].…”
Section: Introductionmentioning
confidence: 99%
“…% ZrO2 and SiC+ZrO2 for 6066 AA 58.49% and 92.07% respectively compared to as resave. Karthikeyan et.al [26] they tested the tensile strength of the five LM6 samples with 0%, 3%, 6%, 9%, and 12%, of ZrO2 respectively, and it was evident in their results that the final ultimate tensile stress was obtained for specimen No. 5, which contains about 12.0 % of ZrO2 nano material.…”
Section: Specimen Geometrymentioning
confidence: 99%
“…The failure modes are the first step to identify the type of failure, and fractographic study can be used to establish the failure modes and failure analysis 13 . Features of the nanocomposite failure distinguishes the fracture surface, these features provide vital information that determines the location and source of failure, conditions of stress at the crack initiation time and propagation, and final failure 13,14 . In this work, the fractographic features will characterize tensile…”
Section: Introductionmentioning
confidence: 99%